2018
DOI: 10.1111/wre.12318
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anaerobic soil disinfestation amendment type and C:N ratio on Cyperus esculentus tuber sprouting, growth and reproduction

Abstract: Anaerobic soil disinfestation (ASD) is a cultural technique primarily targeted for control of soilborne plant pathogens, but can also impact weed propagules. A repeated pot study was conducted to evaluate ASD treatment impact on sprouting and growth of introduced Cyperus esculentus (yellow nutsedge) tubers using dry molasses-based and wheat bran-based amendment mixtures at four carbon-to-nitrogen (C:N) ratios (from 10:1 to 40:1) and compared with a nonamended control. The mean percentage of sprouted tubers rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 32 publications
3
28
0
Order By: Relevance
“…To our knowledge, this is the first study to specifically evaluate ASD amendment C:N ratio effects on soil inorganic N, crop N status and crop yield. At the same time, our results are consistent with other reports of high soil inorganic N following soil disinfestation with ASD amendments with relatively low C:N ratios (Butler et al, 2014a;McCarty et al, 2014;Di Gioia et al, 2017;Shrestha et al, 2018b). Soil microbial stoichiometry is fairly constrained within a C:N ratio of ∼5:1 to 7:1, which along with microbial energetic needs causes substrate C:N ratios above ∼20:1 to lead to N limitations on microbial decomposition and reduced available soil inorganic N (Sinsabaugh et al, 2013;Spohn, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, this is the first study to specifically evaluate ASD amendment C:N ratio effects on soil inorganic N, crop N status and crop yield. At the same time, our results are consistent with other reports of high soil inorganic N following soil disinfestation with ASD amendments with relatively low C:N ratios (Butler et al, 2014a;McCarty et al, 2014;Di Gioia et al, 2017;Shrestha et al, 2018b). Soil microbial stoichiometry is fairly constrained within a C:N ratio of ∼5:1 to 7:1, which along with microbial energetic needs causes substrate C:N ratios above ∼20:1 to lead to N limitations on microbial decomposition and reduced available soil inorganic N (Sinsabaugh et al, 2013;Spohn, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…The C/N ratio is a key factor in RSD treatment (Liu et al, 2016;Shrestha et al, 2018). The results of NH + 4 -N content analysis showed that higher C/N ratios were associated with lower NH + 4 -N contents when the substrate input amount and treatment time were the same.…”
Section: Discussionmentioning
confidence: 99%
“…Significant effort has been targeted toward enhancing ASD efficacy for soil-borne disease control with an emphasis on optimizing implementation variables such as carbon source (Butler et al, 2012; Hewavitharana et al, 2014; Serrano-Pérez et al, 2017; Shrestha et al, 2018), irrigation volume and duration (Daugovish et al, 2015), length of the incubation period, and the effects of soil temperature (Hewavitharana et al, 2015). Concurrent studies have examined the influence of these variables on the proposed mechanisms that yield disease suppression in response to ASD.…”
Section: Introductionmentioning
confidence: 99%